1999
DOI: 10.1034/j.1399-302x.1999.140104.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oral mitis group streptococci by arbitrarily primed polymerase chain reaction

Abstract: "Mitis group" streptococci are commensal but may play some role in dental caries, septicemia or endocarditis. Rapid genotypic identification would aid studies of dental plaque ecology, or diagnostic use. AP-PCR with 58 unpaired arbitrary primers was used to characterize 7 Streptococcus gordonii, 11 Streptococcus sanguis, 2 Streptococcus crista, 5 Streptococcus parasanguis, 18 Streptococcus oralis, and 36 Streptococcus mitis (22 biovar 1 and 14 biovar 2). S. parasanguis 16S rRNA variable region primer RR2 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
1
22
0
1
Order By: Relevance
“…It has been shown that the polymorphism in length of the amplified sequences (amplicons) of RAPD fingerprints obtained by AP-PCR can be used to compare bacterial strains [22][23][24], including the groups of mutans streptococci [28,29] and mitis streptococci [30]. In the present study, this application of RAPD analysis to genotyping of oral streptococci confirmed that the RAPD assay can distinguish the species S. mutans and S. sobrinus from each other.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It has been shown that the polymorphism in length of the amplified sequences (amplicons) of RAPD fingerprints obtained by AP-PCR can be used to compare bacterial strains [22][23][24], including the groups of mutans streptococci [28,29] and mitis streptococci [30]. In the present study, this application of RAPD analysis to genotyping of oral streptococci confirmed that the RAPD assay can distinguish the species S. mutans and S. sobrinus from each other.…”
Section: Discussionsupporting
confidence: 55%
“…They include DNA-DNA hybridisation [1,12,14], restriction endonuclease analysis (REA) [16][17][18][19], multilocus enzyme electrophoresis (MLEE) [20], ribotyping, PCR and colony hybridisation with DNA probes [21]. A PCR-based procedure of DNA fingerprinting, called arbitrarily primed PCR (AP-PCR) [22] or randomly amplified polymorphic DNA (RAPD) analysis [23], has been applied to strain identification and typing of oral bacteria [24][25][26][27], oral streptococci [28][29][30] and non-oral streptococci [31][32][33][34]. The present study used RAPD analysis for typing S. mutans and S. sobrinus strains and to explore the potential of this typing method to distinguish these from the other taxa that comprise the group of mutans streptococci.…”
Section: Introductionmentioning
confidence: 99%
“…Our results using both primers described by Rudney and Larson (32), and also both primers together with additional primers (OPRs), indicated a varied degree of similarity among the S. crista strains studied herein. The results using the latter method (combination of primers) showed a lower similarity among strains than that obtained when only the RR2 and 434 primers were used.…”
Section: Discussionmentioning
confidence: 71%
“…The purpose of this work was to biologically characterize different S. crista strains obtained from the dental biofilm of different adult individuals seen at the Dental Clinic of São Francisco University, Bragança Paulista, SP, Brazil by means of molecular techniques, and to compare the results with those published by other groups (3,6,(7)(8)(9)13,18,19,32,44). To the best of our knowledge, no other research group has published in Brazil, any characterization of these types of strains regarding their molecular profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation